Analisis Promosi Jabatan Pegawai Bank Syariah Indonesia KCP Muara Bulian - Subhan, Muhammad; Miftah, AA; Afril Lestari, Windi (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This paper aims to determine the implementation system, the factors that influence, and the impact of promotion on employee performance improvement at Bank Syariah Indonesia KCP Muara Bulian. This thesis uses a qualitative approach with data collection methods through interviews and documentation. Based on the research conducted, the following results were obtained: First, the system for implementing employee promotion at Bank Syariah Indonesia KCP Muara Bulian has been implemented according to company procedures such as criteria or conditions, assessment, and no bribes or factors of closeness to superiors because of the provisions in giving Promotion of positions for employees is determined by Central Bank Syariah Indonesia. Second, factors that influence employee promotion at Bank Syariah Indonesia KCP Muara Bulian are honesty and responsibility, loyalty, experience and work performance as measured by the amount and quality of financing distributed. Third, the impact of job promotion on improving employee performance at Bank Syariah Indonesia KCP Muara Bulian is the emergence of work enthusiasm and motivating employees to improve better performance and from the results of this performance an increase in the number of customers and financing every year